Legitimizing Intimate Partner Violence: Moral Evaluations, Attribution of Responsibility, and (Reduced) Helping Intentions. Issue 5 (March 2021) - Pagliaro, Stefano; Pacilli, Maria Giuseppina; Giannella, Valeria Amata; Giovannelli, Ilaria; Spaccatini, Federica; Baldry, Anna Costanza
This article examines the influence of moral evaluations and attribution of responsibility on individuals' willingness to provide help if witnessing an intimate partner violence (IPV) episode. A total of 121 undergraduates read a fictitious article from a newspaper, allegedly describing an IPV episode. According to the experimental condition, participants read that the victim had either admitted infidelity or denied it. After reading the newspaper article, participants evaluated the victim on several dimensions (i.e., morality, competence, and sociability), rated the extent to which they deemed her responsible for the violence (i.e., the internal attribution of what happened), and expressed their willingness to provide help and support to the victim herself. In the admission condition, the victim was evaluated as less moral and more responsible for the episode of IPV. These evaluations, in turn, lowered the willingness to provide help to the victim. This study confirmed the role of moral evaluations and internal attribution on bystanders' reaction, and we present practical implications for intervention in a field, IPV, in constant need of updated validated evidence for efficient prevention strategies.